Capital Market Valuation of the Terms of Office of the Chief Executive Officers of Deutsche Telekom After the Initial Public Offering - Torsten J. Gerpott; Roman Schwetz (Wirtschaftsdienst)
Abstract Assuming that CEOs significantly shape a firm’s strategic positioning, the present study looks at two stock-exchange valuation criteria of the largest German telecommunications network operator, Deutsche Telekom, to reflect on the performance of the four CEOs leading the firm since its Initial Public Offering in 1996. The criteria are the average annual change rate of Deutsche Telekom’s (1) share price and (2) market capitalisation during a CEO’s term of office. The two measures are compared between the CEOs and with eight benchmarks (three stock indices, big-five tech companies). Results suggest that (1) Deutsche Telekom’s present CEO outperforms his predecessors mainly due to a clear emphasis on Deutsche Telekom’s mobile communication business in the US and (2) the CEO-independent lower value of Deutsche Telekom relative to Google, Apple, Meta, Microsoft, Amazon and other large over-the-top platform providers cannot be remedied through network access fees/cost contributions imposed on OTT companies.